ANALYSIS OF THE IMPACT OF MONETARY AND FISCAL POLICIES ON THE INDONESIAN ECONOMY - Wahbi , Abdul Azim; Syahrudi (International Journal of Accounting Innovation, 2025)
Objective: This study aims to analyze the impact of monetary and fiscal policies on the Indonesian economy using the literature review method. Method: This study aims to analyze the impact of monetary and fiscal policies on the Indonesian economy using the literature review method. Results: The results show that monetary policy through money supply regulation is significant in promoting economic growth, while fiscal policy is effective in supporting economic recovery through increased government spending, social assistance, and tax cuts during the pandemic. Novelty: This study emphasizes the importance of coordinated implementation of monetary and fiscal policies in Indonesia, particularly during economic crises such as the COVID-19 pandemic, by highlighting their complementary roles in promoting growth and recovery.